1998
DOI: 10.1016/s1350-4487(97)00205-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of crushing and additive irradiation procedures on EPR dosimetry of tooth enamel

Abstract: -The effect of the crushing and additive dose procedures used in EPR dosimeuy of enamel was studied on the signals with g-factors of 2.0045 and gl = 2.0018, g, = 1.9975. Eight~tions,~g~g fi size from <75 micrometers to 2 mm, were prepared from one tooth. Two cases wem investigated: crushing of a non-irradiated sample and of a sample previously irradiated (6 Gy tinm Wo gamma ray source). In the non-imadiated study, the intensity of the native signal at 2.0045 inaeased by circa 1.75 times as the grain size &cmas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…Grinding was found to intensify the native signal in some cases (Fattibene et al, 1998;Sholom et al, 1998a;Aldrich et al, 1992;Desrosiers et al, 1989), but there is no conclusive evidence that this is a real growth of the native signal and not a generation of a different, although closely resembling, signal. Polyakov et al (1995) went as far at to propose that the native signal was due to grinding, in view of the increase in intensity and line width with prolonged grinding that resulted in smaller grain size (their g-value of 2.0038, most likely, should be corrected).…”
Section: Effect Of Mechanical Treatmentmentioning
confidence: 97%
See 4 more Smart Citations
“…Grinding was found to intensify the native signal in some cases (Fattibene et al, 1998;Sholom et al, 1998a;Aldrich et al, 1992;Desrosiers et al, 1989), but there is no conclusive evidence that this is a real growth of the native signal and not a generation of a different, although closely resembling, signal. Polyakov et al (1995) went as far at to propose that the native signal was due to grinding, in view of the increase in intensity and line width with prolonged grinding that resulted in smaller grain size (their g-value of 2.0038, most likely, should be corrected).…”
Section: Effect Of Mechanical Treatmentmentioning
confidence: 97%
“…As a consequence, it is now accepted not to use grain sizes smaller than 150 µm. However, the situation may be more complex than presented by Sholom et al (1998a). Iwasaki et al (1993) reported a 10% higher radiation response for grains smaller than 75 µm in samples irradiated before grinding, which was attributed to an underlying distortion of the baseline between 0 and 500 mT.…”
Section: Parameters Affecting the Sensitivity Of Tooth Enamel To Radimentioning
confidence: 97%
See 3 more Smart Citations